The Challenge in Madrasah Management in Achieving Sustainability and Advantages in the Technological Digital Era - Luneto, Buhari (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2022)
This paper aims to discuss the problems faced in managing madrasas, particularly in achieving high competitiveness in the current era of digital technology. This study uses exploratory descriptive data according to the theme and research objectives. The research data were analyzed through in-depth evaluation and interpretation of the data, so that relevant important points were found related to the discussion of challenges and competitiveness faced by school management in modern times. This study found that the governance of Islamic schools faces various challenges, due to the fact that technology and the digital era are globalization trends that have positive and negative impacts. Madrasas as places where the pillars of Islam are in achieving educational goals based on Islam are expected to be able to take advantage of all these technologies by well, namely by balancing and aligning globalization trends, so as to give birth to creativity and active learning for students in facing competitiveness in today's global world. Tulisan ini bertujuan untuk membahas permasalahan yang dihadapi dalam mengelola madrasah khususnya dalam mencapai daya saing yang tinggi di era teknologi digital saat ini. Penelitian ini menggunakan eksplorasi data deskriptif sesuai dengan tema dan tujuan penelitian. Data penelitian dianalisis dengan evaluasi mendalam, dan menginterpretasi data sehingga ditemukan poin-poin penting yang relevan terkait dengan pembahasan mengenai tantangan dan daya saing yang dihadapi oleh manajemen sekolah di zaman modern. Kajian ini menemukan bahwa tata kelola sekolah Islam menghadapi berbagai tantangan, disebabkan karena teknologi dan era digital ini merupakan trend globalisasi yang memiliki dampak positif dan negatif. Madrasah sebagai tempat pilar Islam dalam mencapai tujuan pendidikan yang berlandaskan agama Islam diharapkan bisa memanfatkan semua teknologi tersebut dengan baik, yaitu dengan cara menyeimbangkan dan menyelaraskan trend globalisasi, sehingga melahirkan kreatifitas dan pembelajaran aktif bagi siswa dalam menghadapi daya saing didunia global saat ini.